Experiências de pesquisa e extensão na elaboração do protocolo de consulta e consentimento do território quilombola Alto Trombetas II - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The Alto Trombetas II Quilombola Territory, formed by eight communities derived from the old mocambos created in the 19th century, is located on the banks of the Trombetas River, in the municipality of Oriximiná, in northwestern Pará. The local communities experience disputes and conflicts related to the presence of two federal conservation units and a large bauxite mining project. In 2012, the mining company initiated with the competent bodies an environmental licensing process for plateaus located in the territory, without consulting the communities. The Federal Public Prosecutor's Office opened an investigation into the fact, and the mining company's work was suspended until prior consultation with the communities was carried out. Composed of complex and conflicting episodes, the consultation process presented countless difficulties, motivating the quilombola association to create a protocol for future similar processes. It is in this context that this paper reports the research and extension experiences developed by an anthropologist in training in the elaboration of the Consultation and Consent Protocol for the Quilombola Territory Alto Trombetas II.
Keywords: Território Quilombola; Consulta prévia; Protocolo de consulta; CNPQ:: CIÊNCIAS HUMANAS